2006
DOI: 10.1136/ard.2006.056937
|View full text |Cite
|
Sign up to set email alerts
|

Sex: a major predictor of remission in early rheumatoid arthritis?

Abstract: Early remission of rheumatoid arthritis by 28-joint Disease Activity Score<2.6 was as frequent or more frequent in this study than in most previous reports. Importantly, women had more severe disease with a considerably lower remission rate than men, although the disease activity before treatment seemed similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
159
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(198 citation statements)
references
References 27 publications
31
159
2
6
Order By: Relevance
“…In particular, we were unable to adjust for the severity of comorbid conditions. Our findings add further support to previous studies that reported a more favorable outcome for male RA patients compared to female RA patients (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). We have also highlighted the importance of examining such questions using longitudinally collected data, and with the aid of novel analytical techniques.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In particular, we were unable to adjust for the severity of comorbid conditions. Our findings add further support to previous studies that reported a more favorable outcome for male RA patients compared to female RA patients (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). We have also highlighted the importance of examining such questions using longitudinally collected data, and with the aid of novel analytical techniques.…”
Section: Discussionsupporting
confidence: 88%
“…It has also been reported that, compared to men, women have a poorer outcome in terms of functional outcome and disease activity (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), although no sex difference in terms of radiographic damage has been reported (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…Results of other studies suggest that women have higher disease activity than men due to the influence of estrogens on the immune system (11,57). Our data show a trend toward a difference between premenopausal and postmenopausal women and men (Table 3).…”
Section: Discussionsupporting
confidence: 66%
“…This finding emphasizes that the long lasting rheumatoid arthritis patients prone the thrombosis. Based on the gender this study showed that the female more affected by rheumatoid arthritis this findings were in a consistence with several studies done in different countries [4] [26] [27] [28] [29] [30]. The most common limitations in this study that the number of cases and shortage of the study duration.…”
Section: Discussionmentioning
confidence: 55%